The Challenges of International Education: Developing a Public Relations Unit for the Asian Region - Fitch, K.; Surma, A. (Journal of University Teaching and Learning Practice, 2006)
Murdoch University’s public relations program attracts a significant number of international students. Up to 60% of students in some units come from Singapore and Malaysia. While many spend at least one year in Australia as part of the three year degree, students in both countries may complete the entire degree offshore from 2007. The authors rewrote a second year public relations unit with the aim of making it more relevant for local and international students. This posed particular challenges in terms of pedagogical and conceptual approaches. For instance, there are cultural and linguistic issues which influence the ways students learn, and which have particular implications for a unit which expressly aims to consolidate students’ professional writing skills. There are also implications for public relations theory, which tends to be dominated by Western concepts and models, and public relations practice, which varies in different countries. This paper offers a reflection on the issues we addressed in the redevelopment of the unit, as well as some suggestions for future teaching and learning practices.